2021
DOI: 10.1212/wnl.0000000000011566
|View full text |Cite
|
Sign up to set email alerts
|

Microbleeds, Cerebral Hemorrhage, and Functional Outcome After Endovascular Thrombectomy

Abstract: Objective—To determine whether pre-treatment cerebral microbleeds (CMBs) presence and burden are correlated with an increased risk of intracranial hemorrhage (ICH) or poor functional outcome following endovascular thrombectomy (EVT) for acute ischemic stroke (AIS).Methods—Consecutive patients treated by EVT for anterior circulation AIS were retrospectively analyzed. Experienced neuroradiologists blinded to functional outcomes rated CMBs on T2*-MRI using a validated scale. We investigated associations of CMB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In a retrospective cohort study of 513 patients treated with stent retriever or aspiration devices, CMB presence or burden on pretreatment MRI was associated neither with symptomatic ICH, nor reperfusion probability or functional outcome in adjusted analyses. 42 A smaller previous observational study reached similar conclusions. 43 Interestingly, a recent retrospective analysis of the German Stroke Registry suggests that patients meeting modified Boston criteria for CAA might also benefit from MT (OR for mRS 0–2 with successful reperfusion: 6.82, 95% CI = 1.77–26.3), with similar rates of post-MT ICH to patients without CAA.…”
Section: Cerebral Small Vessel Disease and Hyperacute Treatment Of Is...supporting
confidence: 67%
“…In a retrospective cohort study of 513 patients treated with stent retriever or aspiration devices, CMB presence or burden on pretreatment MRI was associated neither with symptomatic ICH, nor reperfusion probability or functional outcome in adjusted analyses. 42 A smaller previous observational study reached similar conclusions. 43 Interestingly, a recent retrospective analysis of the German Stroke Registry suggests that patients meeting modified Boston criteria for CAA might also benefit from MT (OR for mRS 0–2 with successful reperfusion: 6.82, 95% CI = 1.77–26.3), with similar rates of post-MT ICH to patients without CAA.…”
Section: Cerebral Small Vessel Disease and Hyperacute Treatment Of Is...supporting
confidence: 67%
“…The AtRial Cardiopathy and Antithrombotic Drugs In Prevention After Cryptogenic Stroke (ARCADIA) trial ( 8 ) and the Apixaban for Treatment of Embolic Stroke of Undetermined Source (ATTICUS) trial ( 39 , 40 ) are specifically randomizing patients with biomarker driven atrial cardiopathy (though different criteria than our study) to anticoagulation vs. antiplatelet therapy and may help answer some of these questions. Atrial cardiopathy may increase subclinical risk of embolic stroke, and with the addition of the findings of this study that risk may be marked by CMB ( 41 ). Future studies should investigate the role of anticoagulation for atrial cardiopathy and also consider whether there are differences in the number of CMB.…”
Section: Discussionsupporting
confidence: 53%
“…It’s noted that there was no significant difference in the safety outcomes when using either of the two scores. Previous studies also showed that the presence of CMBs was not significantly associated with the risk of ICH in patients receiving EVT ( Shi et al, 2016 ; Derraz et al, 2021 ). However, considering the small sample of the study, we should be cautious when interpreting the relationship between SVD burden and the safety outcome.…”
Section: Discussionmentioning
confidence: 82%
“…The association between SVD and the outcome in patients receiving EVT has also been investigated. Among these SVD markers, brain atrophy was reported to be associated with outcome and mortality after mechanical thrombectomy ( Diprose et al, 2019 ; Lauksio et al, 2021 ), whereas cerebral microbleeds not ( Shi et al, 2016 ; Derraz et al, 2021 ). The association between WMH and clinical outcomes has been reported with conflicting results ( Atchaneeyasakul et al, 2017 ; Boulouis et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%